Economic Development, Exchange Rates, and the Structure of Trade - Istvan Konya (Hungarian Academy of Sciences, Institute of Economics, 2005)
The paper builds a two-country open economy model of incomplete exchange rate pass-through. The paper contributes to the existing literature in two ways. First, incomplete pass-through is the result of price discrimination, and not any assumption about price rigidities. The flexible-price model is capable of delivering empirically plausible magnitudes of pass-through, as long as the exchange rate shock is temporary and not very persistent. Second, the model is also used to shed light on the empirically observed differences in exchange rate pass-through between developing and developed countries. In particular, the discrepancy is explained by the different composition of consumption and trade patterns of rich and poor countries - an assumption to which some empirical support is also presented.
Keywords: F12; F31; F41; 330; Exchange rate pass-through; Economic development; International trade